PHASE TRANSITIONS OF SAMANI DATE PALM (PHOENIX DACTYLIFERA L.) FRUIT USING DIFFERENTIAL SCANNING CALORIMETER (DSC) - Zaitoon, Amr M.; Elansari, Atef M.; Ahmed, Yehia S.; Taha, Nahla A. (Emirates Journal of Food and Agriculture, 2017)
The aim of the present study was to investigate the effect of heating rate, annealing condition, and moisture content on the glass transition temperatures (Tg), onset of melting point (Tm), initial freezing point (TF), and enthalpy change during melting (Hm) of Samani dates using Differential Scanning Calorimeter (DSC). Three different heating rates; 1, 5, and 10 °C/min were employed during DSC scan to study its effect on the thermal properties of dates. In addition, Samani samples were annealed for 30 min at -30 °C to study the effect of annealing on the same properties. Different levels of moisture content were also used to study its impact on the same properties. The results showed that as the heating rate increases, the Tg increases significantly (p<0.05). Also, annealing has a significant (p<0.05) effect on Tg and Hm and has no significant effect on Tm and TF values. Tg was decreased with the increase of moisture content, while Tm, TF, and Hm increased significantly (p<0.05) with increasing moisture content. The obtained results can be used to enhance stability of stored dates, maintain quality, and extend shelf life. The procedures developed can establish a protocol to yield phase transitions information for dates using DSC.